Can high-value markets ensure households food security? Evidence from avocado producers in Sidama Region of Ethiopia - Tibebu Legesse; Kehabtimer Kebede; Aneteneh Ashebir; Zerhun Ganewo; Abera Alemu; Andachew Samuel (Cogent Social Sciences, 2024)
Linking farmers to high-value markets continue to be a viable option for breaking the food insecurity. Many studies have emphasized on factors determining smallholders’ participation in high-value markets. Previous studies have methodological limitations since they neglected the associated effects on food security. Therefore, the purpose this study was to fill a knowledge gap by investigating the factors influencing smallholder avocado farmers’ participation in high-value markets and how it impacts households’ food security in the Aleta chuko district, Ethiopia. The primary data was collected from randomly selected 389 avocado producers using a semi-structured questionnaire. Descriptive statistics, inferential statistics, and propensity score matching model were used to analyze the data. The result of the binary logit model revealed that the participation of avocado producers in a high-value market was influenced by age, educational status, the quantity of avocados sold, and price of avocado and market information. The ATT estimation of PSM model indicated that Avocado producers who participated in high-value market channels have higher food security status (by 4.3–4.8%) compared to those who were not. Thus, this study suggested that concerned bodies in Ethiopia should encourage more households to participate in the high-value markets.